Dayak Open-Air Museum Di Pangkalan Bun Sebagai Wahana Konservasi Kebudayaan Masyarakat Kalimantan Tengah - FATHAN FAHRUZI, RENANDIA, Dr. Ir Qomarun, MM, Wisnu Setiawan, ST, M.Arch, Phd (2016)
Open-Air Museum originated from Europe in the mid 19th century, is motivated by the current state of society who are experiencing changes in many areas of life due to the process of industrialization and urbanization. But also lead to start the extinction of local cultural traditions as well as the increasing cultural uniformity in the form of cultural unification. The development of new trend raises concerns mainly intellectuals and encourage them to form a movement to counter it. Pangkalan Bun As one of the cities that have historical value is high, but Pangkalan Bun no container for the history of the culture of their ancestors, the government took the initiative to create a museum to preserve the culture. The author would like to design a museum with an open concept to avoid the impression that the museum is too monotonous and not interactive, using the concept of Traditional Architecture and Architecture Modern.